Расчет трехмерного распределения магнитного поля мощного турбогенератора в режиме холостого хода - Милых, В.И.; Высочин, А.И. (Електротехніка і електромеханіка, 2011)
Results of test calculation of three-dimensional magnetic field of a turbogenerator in the idling mode are presented. The calculation is made with a numerical method taking into account a real turbogenerator design with application of Maxwell 11 package.